Early performance-based and patient-reported outcomes of a contemporary taper fit bone-conserving short stem femoral component in total hip arthroplasty. Issue 4 (April 2017) - Hossain, F.; Konan, S.; Volpin, A.; Haddad, F. S.
Abstract : Aims: The aim of this study was to compare early functional and health related quality of life outcomes (HRQoL) in patients who have undergone total hip arthroplasty (THA) using a bone conserving short stem femoral component and those in whom a conventional length uncemented component was used. Outcome was assessed using a validated performance based outcome instrument as well as patient reported outcome measures (PROMs). Patients and Methods: We prospectively analysed 33 patients whose THA involved a contemporary proximally porous coated tapered short stem femoral component and 53 patients with a standard conventional femoral component, at a minimum follow-up of two years. The mean follow-up was 31.4 months (24 to 39). Patients with poor proximal femoral bone quality were excluded. The mean age of the patients was 66.6 years (59 to 77) and the mean body mass index was 30.2 kg/m 2 (24.1 to 41.0). Outcome was assessed using the Oxford Hip Score (OHS) and the University College Hospital (UCH) hip score which is a validated performance based instrument. HRQoL was assessed using the EuroQol 5D (EQ-5D). Results: There were no major peri-operative complications. There was no difference in the mean post-operative OHS, EQ-5D or function subscale of the UCH hip scores between the two groups. The mean pre-operative OHS and EQ-5D scores improved significantly (all p < 0.001). The mean functional component of the UCH hip score at final follow-up was 42.5 and 40.6 in the short stem and conventional stem groups, respectively. There was no statistically significant difference between the groups (p = 0.42). A total of seven patients (21.2%) in the short stem group and nine (16.98%) in the conventional group achieved a ceiling effect using the OHS; none did using the function subscale of the UCH hip score. Conclusion: The proximally porous coated tapered short stem femoral component achieves comparable short-term functional outcomes when compared with a conventional longer stem uncemented femoral component when THA is undertaken in patients with good bone quality. Cite this article: Bone Joint J 2017;99-B(4 Supple B):49–55.